2021
DOI: 10.1093/mnras/stab2218
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter’s X-ray aurora during UV dawn storms and injections as observed byXMM–Newton, Hubble, andHisaki

Abstract: We present results from a multiwavelength observation of Jupiter’s northern aurorae, carried out simultaneously by XMM-Newton, the Hubble Space Telescope (HST), and the Hisaki satellite in September 2019. HST images captured dawn storms and injection events in the far ultraviolet aurora several times during the observation period. Magnetic reconnection occurring in the middle magnetosphere caused by internal drivers is thought to start the production of those features. The field lines then dipolarize which inj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Such dipolarizations of the field in the middle magnetosphere have been found to be associated with injection events found from HST UV observations and can be accompanied by bright dawn storm emissions (Yao et al., 2020). These bright dawn storm emissions have been found to be correlated with a brightening of HXR intensity in the Jovian aurora (Wibisono et al., 2021), likely linked to similar regions of electron bremsstrahlung activity (e.g., Branduardi‐Raymont et al., 2008). However, we note that the CXO interval was 2–3 Jovian rotations after the reconfiguration of the field and showed no concentrated X‐ray emissions in expected the dawn or LLE regions.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Such dipolarizations of the field in the middle magnetosphere have been found to be associated with injection events found from HST UV observations and can be accompanied by bright dawn storm emissions (Yao et al., 2020). These bright dawn storm emissions have been found to be correlated with a brightening of HXR intensity in the Jovian aurora (Wibisono et al., 2021), likely linked to similar regions of electron bremsstrahlung activity (e.g., Branduardi‐Raymont et al., 2008). However, we note that the CXO interval was 2–3 Jovian rotations after the reconfiguration of the field and showed no concentrated X‐ray emissions in expected the dawn or LLE regions.…”
Section: Resultsmentioning
confidence: 93%
“…The X-ray dawn region is found to coincide with a portion of the ME and the Io footprint suggesting an association between dawn storms, injections of hot plasma from the middle magnetosphere (e.g., Gerard et al, 1994;Kimura et al, 2017) and bright X-ray populations. Recent work by Wibisono et al (2021) found the intensity of the HXRs to increase during the presence of a dawn storm with reduced activity from the more poleward SXRs, utilizing the energy resolution of XMM-Newton. Dawn storms typically have a duration of at least 1-2 hr (e.g., Ballester et al, 1996), therefore our CML thresholding (spanning an interval of 2.5-3 hr during each Chandra observation) will be sufficient to detect the brightest signatures associated with these events, if any.…”
Section: Table 1 Table Of Concurrent Chandra and Hubble Space Telesco...mentioning
confidence: 99%
See 1 more Smart Citation
“…Jupiter generates bright and dynamic ultraviolet (UV) and X‐ray aurorae at its poles. Jupiter's UV aurora are typically grouped into four components: (a) footprints of the Galilean satellites (e.g., Bhattacharyya et al., 2018 ; Bonfond et al., 2009 , 2013 ; Hue et al., 2019 ; Szalay et al., 2018 ), (b) the main emission (e.g., Grodent et al., 2008 ), (c) emissions between the satellite footprints and main emission (e.g., Kimura et al., 2015 ; Mauk et al., 2002 ; Wibisono et al., 2021 ; Yao et al., 2020 ), and (d) emissions poleward of the main emissions (e.g., Grodent, 2015 , and references therein). The main focus of this study is those emissions poleward of the main emission.…”
Section: Introductionmentioning
confidence: 99%
“…This joint observation revealed two key connections between the wavebands: (a) X‐ray bremsstrahlung emissions from precipitating electrons coincide with the UV main emission (Branduardi‐Raymont et al., 2008 ) and (b) X‐ray emissions from precipitating ions coincide with UV flares in the active region (Elsner et al., 2005 ). A recent spectral and timing study of the X‐ray and UV aurora (Wibisono et al., 2021 ) suggested that auroral injection events and dawn storms (Yao et al., 2020 ) may also coincide with an X‐ray bremsstrahlung component. In analyzing the X‐ray, UV, and radio observations from 2007, there was found to be a difference between pulsed/flared X‐ray emissions and a steady “flickering” X‐ray aurorae, with both distinct aurorae produced by precipitating ions (Dunn, Gray, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%